Olfert Ricard og den unge David - Bach-Nielsen, Carsten (Kirkehistoriske Samlinger, 2022)
Dette essay er en let bearbejdelse af en forelæsning ved Selskabet for Danmarks Kirkehistories styrelsesmøde i efteråret 2020. Olfert Ricards klassiker Ungdomsliv fra 1905 tog udgangspunkt i Davidskikkelsen, der i form af franskmanden Antonin Merciés skulptur fra 1872 også kom til at pryde bogen. Den elegante og udfordrende skulptur af David var skabt i opposition mod Tyskland, hvilket svarede til Ricards politiske og nationale holdninger, men lå der mere end et politisk statement i brugen af netop dette signaturbillede? Summary Olfert Ricard (1872-1929) was the most influential leader of the Danish YMCA, a progeny of old Huguenot culture, a liberal Lutheran theologian and a brilliant speaker. He produced a wealth of books such as sermons, devotional books, lectures, and addresses. His book Ungdomsliv, Youth Life from 1905 became an instant success and for many years, it remained an expected gift at young peoples’ confirmations. Its title page was decorated with French sculptor Antonin Mercié’s famous sculpture of the young David of 1872. It would seem relevant as the theme of Ricard’s book was determined by a quotation of 1 Sam about the brilliant young Israelite David. The sculpture however was an anti-German manifestation following the Franco-German War in 1870. In 1879, the owner the Carlsberg Breweries Carl Jacobsen donated a cast of the sculpture to the University of Copenhagen at its quarto centenary, not David in the nude, but in the version with a loincloth. In 1878, The German Empire cancelled the Paragraph 5 in the Peace Treaty of Prague. Until then it secured a future plebiscite in Northern Schleswig. The university consequently transformed its centenary into a Nordic feast – without representatives from Austria and Germany. Mercie’s sculpture of David distinctly reflects the animosity between the old adversaries. Ricard was distinctly anti-German, due to the defeat of 1864 and Denmark’s loss of Schleswig-Holstein. His national attitudes were obvious in the Ungdomsliv. In 1911, Ungdomsliv was translated into German with the title Jugendkraft, but the German editors replaced Mercié’s sensuous French (political) sculpture of David with Verrocchio’s David in Florence just as they omitted the chapter »Your Country« from Ricard’s book. Inspired by Michael Dorsch’s theories of French sculpture following the Franco-German War the essay not only discusses the political implications of the David sculptor in 19th Century Denmark but also the sensuousness and sexual symbolism of the sculpture in relation to Ricard’s bestseller.